Academic standards and gender equality - Živa Kos; Jasna Mažgon; Milica Antić Gaber (Educar, 2024)
This paper provides an analysis of gender equality at the Faculty of Arts of the University of Ljubljana and examines the main results in the broader context of quality in higher education. The Faculty of Arts participated in a project that aimed to develop a gender equality plan for the institution. Data from different aspects of institutional life were collected and analysed to gain a better insight into institutional equality and its relationship with the existing notion of quality in academia, especially through academic career advancement. The study reveals that more women than men tend to remain at the same academic rank for an extended period, particularly at the assistant professor level, and that they meet more objective and subjective obstacles on their academic path. Although there is an increasing awareness of academic policies and practices that foster equality in higher education, there is still a prevalent and strong perception that equality measures compromise academic standards.